Analisis Tingkat Berpikir Siswa Berdasarkan Teori Van Hiele Materi Segi Empat dan Segitiga Ditinjau dari Gaya Kognitif - nurhaolida, nurhaolida; Hayati, Laila; Wulandari, Nourma Pramestie; Azmi, Syahrul (Jurnal Riset Pendidikan Matematika Jakarta, 2022)
This study aims to describe students' thinking levels based on Van Hiele's theory on quadrilaterals and triangles material in terms of reflective and impulsive cognitive styles. The research method used is descriptive qualitative. The subjects in this study were students of class VIII H SMP Negeri 1 Wanasaba. The instruments used are cognitive style tests, geometry tests, and interviews. The results showed that the cognitive style of students in class VIII H of SMP Negeri 1 Wanasaba was generally dominated by students with reflective and impulsive cognitive styles, 71.9% greater than students with fast accurate and slow inaccurate cognitive styles, namely 28.1%. Students with reflective cognitive style are generally at the analysis level (level 1). Reflektive students are able to identify the shapes of quadrilaterals and triangles, are able to determine the names of a quadrilateral and triangular shapes, are able to determine the properties and similarities of the properties. Students with impulsive cognitive style are generally at the visualization level (level 0). Impulsive student at this level are able to identify rectangular and triangular and are able to determine the names of flat shapes correctly but not yet complete.